Electron temperature gradient drift instability in the finite beta edge plasma of a field reversed magnetic configuration - Khvesyuk, V.I.; Chirkov, A.Yu. (Вопросы атомной науки и техники, 2008)
Electromagnetic drift instabilities in the plasma of a field reversed configuration are considered with no assumption of adiabatic response of ions and/or electrons in the range of perpendicular wave number values from k┴ < 1/ρTi up to k┴ ~ 1/ρTe (ρTi and ρTe are ion and electron thermal gyroradiuses). Stabilization by finite plasma length is studied. Stabilising effect of low temperature gradients on electron mode is discussed. Электромагнитные дрейфовые неустойчивости впервые рассматриваются для плазмы обращенной магнитной конфигурации без использования приближения адиабатического отклика ионов и/или электронов в диапазоне значений перпендикулярного волнового числа от k┴ < 1/ρTi до k┴ ~ 1/ρTe (ρTi и ρTe – ионный и электронный тепловые гирорадиусы). Исследуется стабилизация конечной длинной плазмы. Обсуждается стабилизирующий эффект низких градиентов температуры на электронную моду. Електромагнітні дрейфові нестійкості вперше розглядаються для плазми зверненої магнітної конфігурації без використання наближення адіабатичного відгуку іонів і/або електронів у діапазоні значень перпендикулярного хвильового числа від k┴ < 1/ρTi до k┴ ~ 1/ρTe (ρTi і ρTe – іонний і електронний теплові гірорадіуси). Досліджується стабілізація кінцевою довжиною плазми. Обговорюється стабілізуючий ефект низьких градієнтів температури на електронну моду.